2009
DOI: 10.1111/j.1553-2712.2009.00504.x
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Emergency Medical Technician‐Basic (EMT‐B) Exam Score, Length of EMT‐B Certification, and Success on the National Paramedic Certification Exam

Abstract: Objectives: Factors that affect success on the national paramedic certification examination have been identified. However, there are no known studies that have examined success on the paramedic exam with respect to either Emergency Medical Technician-Basic (EMT-B) examination score or length of EMT-B certification (which may reflect field experience gained prior to enrolling in paramedic training). The objectives of this study included assessing the relationship of EMT-B examination score and length of EMT-B c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Program performance and overall success are difficult to define, assess, and track. Early work focused on the innate challenges associated with paramedic program education 13–17 . Margolis et al identified high performing paramedic educational programs and described subjective characteristics of paramedic programs, such as maintaining high‐level entry requirements and fostering a culture that values continuous review and improvement 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Program performance and overall success are difficult to define, assess, and track. Early work focused on the innate challenges associated with paramedic program education 13–17 . Margolis et al identified high performing paramedic educational programs and described subjective characteristics of paramedic programs, such as maintaining high‐level entry requirements and fostering a culture that values continuous review and improvement 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Early work focused on the innate challenges associated with paramedic program education. [13][14][15][16][17] Margolis et al identified high performing paramedic educational programs and described subjective characteristics of paramedic programs, such as maintaining high-level entry requirements and fostering a culture that values continuous review and improvement. 18 Most recently, studies have evaluated paramedic program success as defined by first and cumulative third certification pass rates.…”
Section: Discussionmentioning
confidence: 99%
“…Early work completed before mandatory national accreditation focused on innate challenges associated with paramedic program education. [13][14][15][16][17] Margolis, et al identified high-performing paramedic programs and described their subjective characteristics, such as maintaining high-level entry requirements and fostering a culture that values continuous review and improvement. 6 This focus was amplified by the community direction toward national accreditation as a first step in improving paramedic education.…”
Section: Discussionmentioning
confidence: 99%
“…Research regarding educational factors and personal characteristics that affect entry level competency within EMS has been conducted. [5][6][7][8][9] However, there is very limited research assessing the continued competency of EMS professionals. A majority of the continued competency literature focuses on skill degradation, knowledge retention, and educational interventions.…”
mentioning
confidence: 99%